Seasonal to decadal variability and persistence properties of the Euro-Atlantic jet streams characterized by complementary approaches - H. Banderier; H. Banderier; A. Tuel; T. Woollings; O. Martius; O. Martius; O. Martius (Weather and Climate Dynamics)
Recent studies have highlighted the link between upper-level jet stream dynamics, especially the persistence of certain jet configurations, and extreme summer weather in Europe. The weaker and more variable nature of the jets in summer makes it difficult to apply the tools developed to study them in winter, at least not without modifications. Here, to further investigate the link between jets and persistent summer weather, we present two complementary approaches to characterize the jet dynamics in the North Atlantic sector and use them primarily on the Northern Hemisphere summer circulation.